If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -16 = 4x + -3 Reorder the terms: -16 + 5x = 4x + -3 Reorder the terms: -16 + 5x = -3 + 4x Solving -16 + 5x = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -16 + 5x + -4x = -3 + 4x + -4x Combine like terms: 5x + -4x = 1x -16 + 1x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 -16 + 1x = -3 + 0 -16 + 1x = -3 Add '16' to each side of the equation. -16 + 16 + 1x = -3 + 16 Combine like terms: -16 + 16 = 0 0 + 1x = -3 + 16 1x = -3 + 16 Combine like terms: -3 + 16 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| x-1/5x=64 | | 2(4+3x)=2(2x+5) | | 7(3x+13)+4(x+9)=252 | | 3/5(x=y)-1/5(x-1)= | | x+(x*.14)=700 | | y=(4x+7)(3x-8) | | 235=5(x-50)+60 | | 2=144 | | 5y/7-9/14=y/2 | | 5a^2b^6/20a^4b^2 | | 5-9[5-(8y-7)]= | | -16t^2+48t+30=0 | | 7/9x-5/6x=2 | | (2x-3)-(5x-5)= | | 3z-4=12 | | 3z-4=7.5 | | (2x-3)+(5x-5)= | | 3z-4=9 | | x+2+x=210 | | 2j-1=9 | | 9b^4-16=0 | | 7w+4x-4y-x-2w+3y-3x+4w= | | 2x+2=-11 | | 1+6x=7x-4 | | (9x+2)=3x-22 | | 32(x-1)=-8(4x-x)+24x | | 7(x-7)=7x+14 | | (9x+2)=3x-23 | | 12m-12m=2(-12+12m)-12(10-10m) | | 3r-3=6 | | (x-4)(x^2+6x-1)= | | 20y+18x=10-18x |